Self-medication in medical students: A systematic review (Research, Society and Development, 2023)
Introduction: self-medication is defined as the act of using medicines on one's own or through the indication of disabled people, or even based on common sense or own experience, using the purpose of treating diseases whose symptoms are identified by the individual, without there is a prescription and supervision by a medical professional, dentist or pharmacist. Objective: to carry out a literature review regarding the prevalence of self-medication in medical students. Methodology: this is a systematic review, with studies published between January 2018 and August 2023, in the VHL, Medline, Lilacs and IBCS databases. Results: The sample of this research was made up of 16 articles, in English, Portuguese and Spanish, where it was possible to demonstrate high rates of self-medication in medical students in several countries. Final considerations: it was considered that the proposed objectives were achieved, which revealed the constant presence of self-medication in this public, in addition, it was possible to identify the sociodemographic profile of these students, the reasons why they lead them to carry out such a practice, as well as their sources information about medications and their knowledge about the risks of self-medication.